Enhancing security in portable solar power supply design for alternative energy applications - Syafii Syafii; Benny Dwika Leonanda; Novizon Novizon; Rindina Armysa (Institute of Advanced Engineering and Science, 2026)
Access to reliable electricity remains a challenge in remote and off-grid areas, where conventional power sources are often unreliable or unavailable. This paper presents the design and development of an internet of things (IoT) system for monitoring and securing a portable solar power station tailored for alternative energy applications. The system, which can be recharged using photovoltaic energy sources, employs a coulomb counting method to accurately estimate the battery's state of charge (SoC) and prevent overcharging and overdischarging. The portable power supply provides stable direct current (DC) outputs (5 V, 12 V, 24 V) and an alternating current (AC) output for various remote area applications, including telecommunications and household use. A dual-relay mechanism is used for battery protection: one relay disconnects charging at 100% SoC and reactivates at 70%, while the other disconnects the load at 20% SoC to avoid deep discharge. IoT connectivity enables real-time monitoring and remote control via smartphone. This development promotes efficient energy management, battery longevity, and improved access to sustainable electricity in underserved regions.